Event Study of State-Owned Bank Stock Prices Before and After the Announcement of Danantara on February 24, 2025 - Zaenudin, Windi; Syarief, Mochamad Edman (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This research seeks to examine the variations in stock prices movements and trading activity of state-owned banks (BMRI, BBRI, BBNI, and BBTN) surrounding the announcement of the establishment of the Sovereign Wealth Fund